Alternating donor–acceptor indigo-cyclopentadithiophene copolymers: competition between excited state conformational relaxation, energy transfer and excited state proton transfer. (12th December 2017) - Pina, João; Alnady, Mohamed; Eckert, Anika; Scherf, Ullrich; Seixas de Melo, J. Sérgio
Abstract : In a copolymer with indigo and CPDT, fast ESPT and/or intrachain energy transfer are observed whereas conformational relaxation is absent. Abstract : A comprehensive characterization of the electronic excited states of an alternating donor–acceptor indigo-[didodecyl-cyclopentadithiophene] copolymer (IndC12 CPDT) together with a model compound (with one indigo unit and two C12 CPDT units) was undertaken. The two chromophoric units of the copolymer, indigo and C12 CPDT, were independently investigated. The study encompasses qualitative absorption, fluorescence, phosphorescence emission and transient singlet–singlet and triplet–singlet difference spectra, together with quantitative measurements of quantum yields and lifetimes. The excited state dynamics of the trimeric model compound and copolymer was investigated in solution and in the solid state. Namely the competition of conformation relaxation processes with energy transfer/migration between the didodecyl-cyclopentadithiophene moiety (donor) and indigo (acceptor) units, together with the occurrence of fast excited state proton transfer (ESPT, from the N–H to the CO group of indigo units), was observed. Our results demonstrate that ESPT and intrachain energy transfer are competitive processes in the IndC12 CPDT copolymer excited state both in solution and in the solid state while conformational relaxation was found to be absent.